2014
DOI: 10.5114/wiitm.2014.41599
|View full text |Cite
|
Sign up to set email alerts
|

A complex case of abdominal pain in a patient with pelviureteric junction obstruction.

Abstract: Pelviureteric junction (PUJ) obstruction is a condition frequently encountered in both adult and pediatric patients. Congenital abnormalities and crossing lower-pole renal vessels are the most common underlying pathologies in both men and women. This report presents a case of a young woman who was complaining of intermittent abdominal pain in whom right-sided hydronephrosis was diagnosed. The patient was scheduled for a laparoscopic right-sided Anderson-Hynes pyeloplasty. During the procedure a partly extraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The most common extrinsic factor of UPJO is the presence of CV. 1,4,5,7 In the literature, they are described as an artery or an artery and a vein supplying the lower pole of the kidney. Localized at the height of the UPJ, they can cause mechanical obstruction and the occurrence of a symptomatic hydronephrosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common extrinsic factor of UPJO is the presence of CV. 1,4,5,7 In the literature, they are described as an artery or an artery and a vein supplying the lower pole of the kidney. Localized at the height of the UPJ, they can cause mechanical obstruction and the occurrence of a symptomatic hydronephrosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Less-frequently given reasons for UPJO include high abduction, ureteral twist or adhesions in the retroperitoneal space. [4][5][6] A bundle of CV supplying the lower pole of the kidney and causing mechanical obstruction of the UPJ has been the subject of many discussions. Particularly debatable aspects include the detection rate and a method for dealing with recognized CV and the accompanying hydronephrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Other intrinsic factors which may be included in the etiology of UPJO are stenosis, valves or fibroepithelial polyps [ 2 ]. There are also extrinsic factors such as fibrous bands and crossing vessels which may lead to ureteropelvic junction obstruction [ 3 ]. It is indicated that especially lower pole crossing vessels may play an important role in the etiology of UPJO [ 4 ].…”
Section: Introductionmentioning
confidence: 99%